A Planning Support Tool for Scenario Analysis of Low Carbon Transport Plans in a Data-Poor Context - Shrestha, R. (CRC Press, 2020)
Climate change is a global issue that needs to be addressed by both developed and developing countries. Nevertheless, it is being ignored in many developing countries because of their urgent need to give preference to development activities (Halsnæs and Verhagen, 2007). In addressing this dilemma, the notion of low-carbon development (LCD) has emerged from the discourse on climate change (Tilburg et al., 2011). Definitions of LCD commonly mention reducing CO2 emis-sions, intensive use of low-carbon energy sources and ensuring economic growth by reconciling national mitigation priorities with national development needs (Tilburg et al., 2011; Yuan et al., 2011). One key mitigation strategy is to lower their carbon footprint in cities and make them more sustainable.